The Effect of Gallium Nitrate on Arresting Blood Flow from a Wound - Paul H. Goodley; Moshe Rogosnitzky (Case Reports in Medicine)
A novel application of gallium nitrate, hitherto unreported, in reducing bleeding time from an open wound is presented. Experiments performed using simple punctures in the forearm demonstrated a very substantial reduction in bleeding time when a solution of gallium nitrate was applied relative to a control. This outcome was shown to be unaffected by the anticoagulant properties of warfarin. The mechanism for such action of gallium nitrate is unknown and merits further investigation, as do the possibilities for such an application to improve both civilian and defense trauma treatment modalities.